Integrins and Their Extracellular Matrix Ligands in Lymphangiogenesis and Lymph Node Metastasis - Jie Chen; J. Steven Alexander; A. Wayne Orr (International Journal of Cell Biology)
In the 1970s, the late Judah Folkman postulated that tumors grow proportionately to their blood supply and that tumor angiogenesis removed this limitation promoting growth and metastasis. Work over the past 40 years, varying from molecular examination to clinical trials, verified this hypothesis and identified a host of therapeutic targets to limit tumor angiogenesis, including the integrin family of extracellular matrix receptors. However, the propensity for some tumors to spread through lymphatics suggests that lymphangiogenesis plays a similarly important role. Lymphangiogenesis inhibitors reduce lymph node metastasis, the leading indicator of poor prognosis, whereas inducing lymphangiogenesis promotes lymph node metastasis even in cancers not prone to lymphatic dissemination. Recent works highlight a role for integrins in lymphangiogenesis and suggest that integrin inhibitors may serve as therapeutic targets to limit lymphangiogenesis and lymph node metastasis. This review discusses the current literature on integrin-matrix interactions in lymphatic vessel development and lymphangiogenesis and highlights our current knowledge on how specific integrins regulate tumor lymphangiogenesis.